Potential energy savings and CO2 emissions reduction in Colombia compressed air systems (2019)
Compressed air (CA) is one of the most common systems used in industry. In countries such as Australia, Italia, France, China and USA, energy consumption of CA systems (CASs) contributes about to 10% of the total electricity consumption in industry. In Colombia, this value reaches 8%, highlighting the textile industry, with a 24% of consumption. Despite of all its advantages, CA is expensive, between 10 and 30% of consumed energy reaches the end-use point. Improvements to CASs can achieve between 20 and 60% of energy savings, with pay-back periods lower than two years. These are the reasons that they can be considered as one of the main targetsystems while planning energy efficiency actions in industry. Colombia through different strategies has proposed to implement a group of measures to improve energy efficiency and reduce electricity consumption to 2021 around 7%. Implementation of good practices in CASs is one of them. This paper is showed the share cost, electricity consumption and the savings potential of the CASs in the different divisions of the Colombian manufacturing sector, the main sectors to be involved as well as the potential savings and reduction of dioxide carbon emissions.